Oil Price Pass-Through to Disaggregated CPI Data of Pakistan: Evidence from VAR Approach - Talah Numan Khan, Wasim Shahid Malik (JSSH, 2017)
The aim of this paper is to investigate the oil pass-through to aggregate CPI and disaggregated CPI inflation in Pakistan. We estimated recursive VAR model to investigate the oil price pass- through to CPI and disaggregated CPI inflation for the period of July 1991 to April 2017. The major finding of the study are: (1) oil price shock has moderate effect on CPI inflation; (2) oil price pass- through is high in energy, nonfood, transport and WPI inflation as compared to food, non-energy, housing sector and aggregate CPI inflation; (3) oil price pass-through is high after the period of 2006 when government approved authority to OGRA to notify petroleum products;(4) oil price pass-through has asymmetric effect on disaggregated CPI inflation.